The Effect of Coconut Shell Activated Carbon Dosage on the Removal of Remazol Brilliant Blue R - Alya Zettira Sayyida Sulaeman; Deika Irham Faza Al-Ghaniy; Herawati Budiastuti; Tifa Paramitha (Jurnal Serambi Engineering, 2026)
Textile wastewater contains Remazol Brilliant Blue R (RBBR), a persistent synthetic dye that is difficult to degrade naturally. This study aimed to characterize coconut-shell activated carbon, determine the most effective adsorbent dose and contact time for RBBR removal, and evaluate Pseudo First Order (PFO) and Pseudo Second Order (PSO) kinetic models. The activated carbon was prepared by carbonization at 700°C for 2 h followed by activation with 10% (w/v) H₃PO₄ for 24 h. Batch adsorption used 100 mL of 50 ppm RBBR at adsorbent doses of 0.5–5 g/L and contact times of 5–60 min at 150 rpm. Adsorbent quality was evaluated according to SNI 06-3730-1995 and RBBR concentration was determined by UV–Vis spectrophotometry at λmax 630 nm. All activated-carbon quality parameters met the standard: moisture 4.52%, ash 2.33%, volatile matter 2.60%, fixed carbon 90.55%, and iodine number 856.58 mg/g. The highest Run-2 removal efficiency was 41.68% at 3 g/L and 60 min, leaving 29.2 ppm RBBR. Neither kinetic model consistently described all doses because qt fluctuated with contact time. PFO showed the highest fit at 4 g/L (R²=0.978), while PSO was highest at 5 g/L (R²=0.851). At the optimum dose of 3 g/L, PSO yielded R²=0.447 and was therefore insufficiently representative. The adsorption behavior was also affected by mass transfer and intraparticle diffusion.